Evaluasi Program Pelatihan Tata Rias Pengantin di LKP Sri Tanjung Kota Cilegon - Arini Rizqi Musyafa Ridha; Anita Dahyati; Shabrina Aulia Septiani; Aristu Anan Rizki (Peneliti.net, 2022)
Indonesia has many educational institutions, one of which is an institution that plays a role in improving human resources, namely course and training institutions (LKP). LKP Sri Tanjung is one of the places or places where bridal make-up training programs are held. Training can improve a person's performance if the training is carried out effectively and efficiently. Evaluation is used as material for accountability for the information and decision making that has been provided. Based on this description, this evaluation aims to determine the success or failure of the bridal makeup program in terms of context, input, process, product (CIPP). Evaluators use a qualitative approach with tools and case study methods starting from observation, interviews and documentation. The results of the evaluation obtained in the bridal make-up program at LKP Sri Tanjung, Cilegon City, in the context aspect are in the very good category, the input aspect is in the pretty good category, the process aspect is in the good category, and the product aspect is in the very good category. The results of the evaluation of the Sri Tanjung LKP training program showed that overall it was well implemented, but there is still room for improvement. Keywords: Evaluation, Program, Training, Cosmetology